2016
DOI: 10.3329/bioethics.v7i2.30785
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Service Availability and Readiness Assessment of Non-Communicable Diseases Using the WHO Tool for Gazipur District in Bangladesh

Abstract: Non-communicable diseases (NCDs) disproportionately affect low and middle-income countries where nearly three quarters of NCD deaths occur. Bangladesh is also in NCD burden. This cross-sectional study was done on 50 health facilities centres at Gazipur district in Bangladesh from July 2015 to December 2015 to introduce SARA for better monitoring and evaluation of non-communicable diseases health service delivery. The General Service readiness index score was 61.52% refers to the fact that about 62% of all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 7 publications
3
25
0
Order By: Relevance
“…Our findings are not unique to Saudi Arabia, similar studies were conducted in other countries where marked deficiencies were found in health system infrastructure, workforce capacity, surveillance, planning, policy, and program management. 10 - 13 Our study has revealed that nearly all PHC facilities of category (A and B) could meet the minimum threshold to manage NCDs in line with WHO recommendations. It brings to focus the need to empower category (C) PHC centers to deliver NCD interventions consistent with their level of care as has been carried out elsewhere with satisfactory results.…”
Section: Discussionsupporting
confidence: 64%
“…Our findings are not unique to Saudi Arabia, similar studies were conducted in other countries where marked deficiencies were found in health system infrastructure, workforce capacity, surveillance, planning, policy, and program management. 10 - 13 Our study has revealed that nearly all PHC facilities of category (A and B) could meet the minimum threshold to manage NCDs in line with WHO recommendations. It brings to focus the need to empower category (C) PHC centers to deliver NCD interventions consistent with their level of care as has been carried out elsewhere with satisfactory results.…”
Section: Discussionsupporting
confidence: 64%
“…The questionnaire and variables used in the current study have been published elsewhere. [27][28][29] The data for the 2014-2015 TSPA survey were collected between 20 October 2014 and 21 February 2015, and revisit of some facilities that were not covered previously was conducted from 2 to 13 March 2015. On average, data collection took 1 day for small facilities (dispensary, clinics and some health centres) and 2 or 3 days for large facilities (mostly hospitals).…”
Section: Open Accessmentioning
confidence: 99%
“…The SARA methodology has effectively been used in resource-limited countries to assess: general health facility readiness [31], progress towards universal health coverage [32], maternal and child health services and non-communicable diseases in Bangladesh [33, 34], surgical services in Africa [35], and readiness of Ugandan health services for the management of outpatients with chronic diseases [36]. That said, based on a rigorous internet-based review of literature search, there are no studies that have been conducted to assess the readiness of public health facilities to provide geriatric friendly services in low- and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%